2016
DOI: 10.4103/0300-1652.193860
|View full text |Cite
|
Sign up to set email alerts
|

Quality of acute asthma care in two tertiary hospitals in a state in South Western Nigeria: A report of clinical audit

Abstract: Background:To audit the quality of acute asthma care in two tertiary hospitals in a state in the southwestern region of Nigeria and to compare the clinical practice against the recommendations of the Global Initiative for Asthma (GINA) guideline.Patients and Methods:We carried out a retrospective analysis of 101 patients who presented with acute exacerbation of asthma to the hospital between November 2010 and October 2015.Results:Majority of the cases were females (66.3%), <45 years of age (60.4%), and admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
2
8
3
Order By: Relevance
“…Larger studies are, however, required to validate our scoring method. Notwithstanding, our findings on total adherence are contrasting to the low adherence reported in previous pediatric ( Adeniyi et al, 2017 ) and adult ( Desalu et al, 2016 ) studies in Nigeria. Low adherence to GINA guidelines had been reported among 59.1% resident doctors managing childhood acute asthma exacerbations in a tertiary hospital in Southeastern Nigeria ( Ayuk et al, 2017a ).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Larger studies are, however, required to validate our scoring method. Notwithstanding, our findings on total adherence are contrasting to the low adherence reported in previous pediatric ( Adeniyi et al, 2017 ) and adult ( Desalu et al, 2016 ) studies in Nigeria. Low adherence to GINA guidelines had been reported among 59.1% resident doctors managing childhood acute asthma exacerbations in a tertiary hospital in Southeastern Nigeria ( Ayuk et al, 2017a ).…”
Section: Discussioncontrasting
confidence: 99%
“…However, adherence was good to only documentation of presence of trigger factors and moderate to other recommendations for initial asthma assessment. Desalu et al (2016) reported poor documentation of history/physical examinations and smoking status of adult asthma patients in Nigeria compared to moderate adherence to their documentation in our study. A previous study involving 30 children on emergency admission for acute asthma exacerbations in Lagos, Nigeria showed that trigger factors were documented for 26.7% of the patients ( Okoromah et al, 2006 ), which was far lower than the observed 79.8% in our patients.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations